ASSESSING READABILITY OF READING TEXTS IN ‘BRIGHT’, AN ENGLISH COURSE FOR JUNIOR HIGH SCHOOL STUDENTS - Restynia Rori; Sanerita T. Olii; Aloysius Rettob (JELLT (Journal of English Language and Literature Teaching), 2021)
Textbook is one of media instruction that used in almost every grade level student at the school. Textbook is crucial teaching learning material composed of text or images that is used in many schools and facilitating sequences of learning activities. This title of this study “Assessing Readability of Reading Texts in ‘Bright’, an English Course for Junior High School Students” is taken because predicting readability level of reading texts can help the teachers to match the texts with students in comprehending the material. The causes of this observe is to recognize the clarity degree of studying texts in English language textbooks utilized by trainer. These studies make use of quantitative technique to investigate the information. Twelve studying texts are decided on as studies population. All of decided on texts are analyzed using Flesch Reading Ease method. In this studies, the researchers locate clarity of studying texts with inside the ‘’Bright’’ aren’t appropriate for 9th grade students. Based at the end result of Flesch reading ease method, from 12 reading texts, 9 (75%) studying texts are too Easy for 9th grade students, 3 (25%) studying texts are Standard for 9th grade students. They are three studying texts (25%) appropriate for 9th grade students.